Prioritizing Health Equity: Patient Perspectives from a Clinic-Based PhotoVoice Qualitative Study - Susi L. Keefe; Raie M. Gessesse; Emily R. Lincoln; Kyle Meerkins; Taylor R. Evans (Mary Ann Liebert, 2019)
Purpose: This article explores the results of community-engaged PhotoVoice research with the Family Tree Clinic (FTC) in St. Paul, MN. FTC has >45 years of experience providing sexual, reproductive, and primary health care, with a central mission of overcoming issues for their patients including those of poverty, oppression, lack of access, and discrimination in meeting health care needs. Methods: This research presents the findings of social justice-inspired PhotoVoice focus groups with patients of the clinic that asked two central questions: ?Why do you choose Family Tree Clinic? and ?What stands in the way of achieving your goals for your health?? Results: When health equity is a central priority and evident in clinic culture, practices, and policies, patients articulate positive experiences despite real structural and systemic barriers outside the clinic. Conclusion: We offer suggestions for a health equity-oriented approach to clinic care.